(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
A credit agreement is a debt agreement where the creditor lends a certain amount of funds to the debtor for certain purposes and the debtor is obliged to pay the principal and interest in a predetermined manner and period. In the law of agreement, debtors who are in default are punished to pay compensation to the creditor. The main problem discussed in this thesis is whether the legal consequences of debtors who default on the credit agreement due to the Covid 19 pandemic are a force forward. To answer the main problem, an empirical legal type research was carried out, the nature of the research used was analyzed qualitatively and then described in a descriptive manner, which was intended to obtain a clear and directed picture in order to answer the problem under study. The conclusion from the analysis is that debtors who default on the credit agreement due to the Covid 19 pandemic as a force forward are required to fulfill their obligations but with some relief based on POJK number 11 of 2020. Abstrak Perjanjian kredit adalah suatu perjanjian utang piutang yang dimana kreditur meminjamkan sejumlah dana kepeda debitur untuk keperluan tertentu dan debitur berkewajiban untuk membayar utang pokok serta bunga sesuai dengan cara dan jangka waktu yang telah ditentukan. Dalam hukum perjanjian, debitur yang wanprestasi dihukum untuk membayar ganti rugi kepada kreditur. Pokok permasalahan yang dibahas dalam skripsi ini adalah Apakah akibat hukum debitur yang wanprestasi dalam perjanjian kredit karena pandemi covid 19 sebagai force majuer. Untuk menjawab pokok permasalahan tersebut dilakukan penelitian dengan tipe hukum empiris, sifat penelitian yang digunakan dianalisis secara kualitatif selanjutnya di uraikan secara deskriptif hal yang dimaksudkan untuk memperoleh gambaran yang dapat dipahami secara jelas dan terarah guna menjawab permasalahan yang diteliti. Kesimpulan dari analisis bahwa debitur yang wanprestasi dalam perjanjian kredit karena pandemi covid 19 sebagai force majuer dituntut untuk memenuhi kewajibannya namun dengan beberapa keringanan berdasarkan POJK nomor 11 tahun 2020.